Taxonomic revision of the Australian predaceous water beetle genus Carabhydrus Watts, 1978 (Col. Dytiscidae, Hydroporinae, Hydroporini) - Hendrich, Lars; Watts, Chris H. S. (Zootaxa, 2009)
The present paper treats with the enigmatic Australian predaceous water beetle genus Carabhydrus Watts, 1978 (Dytiscidae, Hydroporinae, Hydroporini) which—except C. stephanieae Watts, Hancock & Leys, 2007—is distributed in forest streams and rivers along the Great Dividing Range of the East Coast and the mountain ranges of SE Australia and Tasmania. The largest species of the genus, Carabhydrus innae sp.n. from southern Victoria and New South Wales, and the smallest, C. storeyi sp.n. from north-eastern Queensland, C. janmillerae sp.n. from south-eastern and C. turaki sp.n. from north-eastern New South Wales are described as new. All species, except C. mubboonus Larson & Storey, 1994, C. niger Watts, 1978 and C. andreas Zwick, 1981, are very rarely collected and mainly known from a few specimens from their type localities. The adults of most species can be found under pebbles and stones and among roots at the edge of running waters, only C. stephanieae has been described from ground water. A key to the ten described species of Carabhydrus is presented, and their distribution and habitats are briefly illustrated.